Lobbying disability in South Africa, 1994-2001 : a description of the activities of the disabled people South Africa (DPSA) in the policy-making process - Tire, Thabo Dennis (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.